Ibiza, Spanien: Zum antiken Bleiglanzabbau am Puig de s’Argentera - Hermanns, Marcus H. (e-Forschungsberichte des DAI, 2023)
This year’s work at the northern foot of Puig de s’Argentera aimed examining the relics of mining activities (like traces of mining driven by fire), analysing their context and gaining first hints concerning their date. Therefore, two campaigns took place, the first for four weeks in April and the second for two weeks in August 2014. After clearing the surface, two archaeological test trenches were dug. This project is part of DAI Cluster II.